1982
DOI: 10.1029/wr018i005p01337
|View full text |Cite
|
Sign up to set email alerts
|

Annual and monthly reservoir operating rules generated by deterministic optimization

Abstract: The development of general reservoir system operating rules by deterministic optimization is investigated in this paper. An algorithm that cycles through a deterministic dynamic program, a regression analysis, and a simulation model is proposed and tested for 48 cases: annual operating rules are determined for 12 cases, and monthly operating rules are determined for 36 cases. The algorithm is easy to use, and each component of the algorithm is relatively simple. The results of using the algorithm for the 48 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(46 citation statements)
references
References 2 publications
0
43
0
3
Order By: Relevance
“…A otimização estocástica implícita emprega um modelo de otimização determinística para operar o reservatório sob vários cenários de afluências igualmente prováveis e, em seguida, examina o conjunto resultante de dados operacionais ótimos a fim de estabelecer as curvas-guia [10], [11], [12], [13], [14], [15], [16]. Os cenários de afluência podem ser selecionados a partir dos registros históricos (quando a série é suficientemente longa), mas são geralmente obtidos por modelos de geração de vazões sintéticas.…”
Section: A Otimização Estocástica Implícitaunclassified
“…A otimização estocástica implícita emprega um modelo de otimização determinística para operar o reservatório sob vários cenários de afluências igualmente prováveis e, em seguida, examina o conjunto resultante de dados operacionais ótimos a fim de estabelecer as curvas-guia [10], [11], [12], [13], [14], [15], [16]. Os cenários de afluência podem ser selecionados a partir dos registros históricos (quando a série é suficientemente longa), mas são geralmente obtidos por modelos de geração de vazões sintéticas.…”
Section: A Otimização Estocástica Implícitaunclassified
“…The maximum social and economic benefits are usually selected as the optimization objective (Dong et al 2007). Currently, the methods most widely used to optimize dam operation are dynamic programming method (Little 1955), multi-objects analysis (Yang and Liu 2001), decomposition and coordination of large scale systems (Turgeon 1981), genetic algorithms (Ahmed and Sarma 2005), and artificial neural networks (Karamouz and Houck 1982). Along with increased human activities in basins, the negative impacts of dams and floodgates on riverine ecology and environments have become more apparent in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Karamouz and Houck [24] showed that 20 storage values could be adequate for a reservoir with storage capacity of up to 170% of the mean annual flow. For convenience of calculation, a number of 21 representative discrete storage values are set evenly.…”
Section: Case Studiesmentioning
confidence: 99%